2021
DOI: 10.1186/s12872-021-02264-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of valvular heart disease in patients with non-valvular atrial fibrillation

Abstract: Background Valvular heart disease (VHD) in non-valvular atrial fibrillation (AF) is a puzzling clinical entity. The aim of this study was to evaluate the prognostic effect of significant VHD (sVHD) among patients with non-valvular AF. Methods This is a post-hoc analysis of the MISOAC-AF trial (NCT02941978). Consecutive inpatients with non-valvular AF who underwent echocardiography were included. sVHD was defined as the presence of at least moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It is well-known to coexist with comorbidities, such as coronary artery disease (CAD), heart failure (HF), valvular heart disease, arterial hypertension, chronic kidney disease, and diabetes mellitus (DM). [6][7][8] AF-related medications are considered high risk regarding side effects and interactions. Prior studies suggest increased mortality and morbidity rates along with an increased pill burden in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known to coexist with comorbidities, such as coronary artery disease (CAD), heart failure (HF), valvular heart disease, arterial hypertension, chronic kidney disease, and diabetes mellitus (DM). [6][7][8] AF-related medications are considered high risk regarding side effects and interactions. Prior studies suggest increased mortality and morbidity rates along with an increased pill burden in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…In another selected AF cohort with at least moderate TR, during a median period of 52 months, the severity of AF-TR was indicative of all-cause mortality [ 25 ]. A post-hoc analysis of MISOAC-AF trial analyzing valvular heart disease in AF patients also confirmed the association of TR with mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 85%
“…Both Dietz et al [ 24 ] and Prapan et al [ 23 ] evaluated composite end-points as adverse events, not mortality alone. Fortuni et al [ 25 ] referred to only a subset of severe TR, respectively, torrential AF-TR, as a driver of mortality, while Samaras et al [ 26 ] evaluated severe TR of all etiologies, not specifically AF-TR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VHD is mainly manifested as valve stenosis or insufficiency, which is the main cause of impaired activity tolerance, heart failure, and death in patients ( 11 ). According to epidemiological statistics in British, at least 50% of people over the age of 65 suffered from VHD ( 25 ).…”
Section: Discussionmentioning
confidence: 99%